Bibliometric: The Role of Science Learning on Student Motivation in Moral Education - Widyaningsih, Mia; Robandi, Babang; Mudzakir, Ahmad (Universal Education, 2025)
The purpose of this research was to find out the development and understanding of the role of science learning on students' motivation in moral education using a bibliometric study on the Google Scholar database with the help of VOS viewer. From 2019 to 2023, 953 articles were found from Google Scholar, and 795 were selected, which were related to content, based on data collection results using the keywords